Electrochemical Characterization of Mancozeb Degradation for Wastewater Treatment Using a Sensor Based on Poly (3,4-ethylenedioxythiophene) (PEDOT) Modified with Carbon Nanotubes and Gold Nanoparticles - Zamora-Sequeira, Roy (2019)
Mancozeb is a worldwide fungicide used on a large scale in agriculture. The active component and its main metabolite, ethylene thiourea, has been related to health issues. Robust, fast, and reliable methodologies to quantify its presence in water are of great importance for environmental and health reasons. The electrochemical evaluation of mancozeb using a low-cost electrochemical electrode modified with poly (3,4-ethylene dioxythiophene), multi-walled carbon nanotubes, and gold nanoparticles is a novel strategy to provide an in-situ response for water pollution from agriculture. Additionally, the thermal-, electrochemical-, and photo-degradation of mancozeb and the production of ethylene thiourea under controlled conditions were evaluated in this research. The mancozeb solutions were characterized by electrochemical oxidation and ultraviolet-visible spectrophotometry, and the ethylene thiourea concentration was measured using ultra-high-performance liquid chromatography high-resolution mass spectrometry. The degradation study of mancozeb may provide routes for treatment in wastewater treatment plants. Therefore, a low-cost electrochemical electrode was fabricated to detect mancozeb in water with a robust electrochemical response in the linear range as well as a quick response at a reduced volume. Hence, our novel modified electrode provides a potential technique to be used in environmental monitoring for pesticide detection